Amateur filmmaking : the home movie, the archive, the web - Rascaroli, Laura; Young, Gwenda; Monahan, Barry (Bloomsbury, 2014)
With the advent of digital filmmaking and critical recognition of the relevance of self expression, first-person narratives, and personal practices of memorialization, interest in the amateur moving image has never been stronger. Bringing together key scholars in the field, and revealing the rich variety of amateur filmmaking, from home movies of Imperial India and film diaries of life in contemporary China, to the work of leading auteurs such as Joseph Morder and Peter Forgacs, Amateur Filmmaking highlights the importance of amateur cinema as a core object of critical interest across an array of disciplines. With contributions on the role of the archive, on YouTube, and on the impact of new technologies on amateur filmmaking, these essays offer the first comprehensive examination of this growing field.